The 2025 Drug Overdose Spike That Wasn't: Neither Politics nor Data Errors Explain the Anomaly. - Post, Lori Ann; Ciccarone, Daniel; Lundberg, Alexander Lars; Mason, Maryann; Sharma, Shivangi; Unick, George Jay; Dasgupta, Nabarun (American Journal of Public Health, 2026)
The article examines a spike in drug overdose deaths in January 2025 according to estimates by the U.S. National Center for Statistics System (NVSS), which reversed the national downward trend. It discusses the revision of the NVSS algorithm used to account for incomplete autopsies and national projections that is said to contradict evidence of continuing declines, and the sudden restrictions in other federal data sources. It describes the impact of the opioid fentanyl on the overdose epidemic.